Oesophageal motility and gastro-oesophageal reflux before and after healing of reflux oesophagitis. A study using 24 hour ambulatory pH and pressure monitoring. - Timmer, R (1994)
In this study 24 hour oesophageal pH and pressure monitoring was used to assess oesophageal motility and acid clearance in 27 patients with reflux oesophagitis (Savary-Miller grades I-IV), before and after healing of oesophagitis. After the first 24 hour study patients were treated with omeprazole 40 mg for 8-24 weeks. After endoscopically verified healing and withdrawing omeprazole for four days 24 hour monitoring was repeated. A total of 106,630 pressure events was analysed. No significant differences were found for any of the motility variables, especially the number and the type of contractions, the peristaltic amplitude, duration, and propagation velocity did not show any changes. Separate analysis of motility variables before and after healing in the low and high grade oesophagitis groups yielded similar results. Oesophageal motor response to reflux was investigated by analysis of all contractions occurring in the two minute period after the onset of each reflux episode. Both motor response and oesophageal acid exposure (% time pH < 4, number of reflux episodes) did not change after healing of oesophagitis, thus implying that acid clearance remained unchanged. These results indicate that impaired motility in reflux oesophagitis is either an irreversible consequence of oesophageal inflammation, or a (pre-existent) factor in its pathogenesis.